THE ANALYSIS OF SATURATED HYDRAULIC CONDUCTIVITY ON YELLOW BAMBOO (Bambusa vulgaris schard Es.J.C) STICK - Perucha, Jenni Aulia (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This research aims to determine the value of saturated hydraulic conductivity (Ks) yellow bamboo in various treatments as a tool for subsurface irrigation purposes. This research has been conducted on March until April 2015. This research was conducted in the Laboratory of Power and Agricultural Machinery, Agricultural Engineering Department, Faculty of Agriculture, University of Lampung. The Ks of yellow bamboo research conducted on6 treatments , those are the epidermis andendodermis thatnot scraped( C1 ); layers of the epidermis and endodermis scraped until 0,5 cmthickness ( C2 ); layers of the epidermis and endodermis scraped up as thick as 0,7 cm ( C3 ); layers of the epidermis and endodermis scraped up as thick as 0,9 cm ( C4 ); layers of the epidermis and endodermis scraped up as thick as 1,1 cm ( C5 ); layers of the epidermis and endodermis scraped up as thick as 1,3 cm(C6 ), thenall treatments is performed in three repetitions and endurance for5weeks.Based onthe research that has beendone , theKs of yellowbamboowith C1 treatment is 0 cm/sec, C2was 7,24 x 10-8 cm/ sec; C3 was 6,87 x 10-8 cm/sec; C4was 8,56 x 10-8 cm/sec; C5was 6,93 x 10-8 cm/sec; and C6was 7,06 x 10-8 cm/ sec. It canbe showthat the higher bamboo’swater absorbing ability the higher hydrolic conductivity’s value that obtained. Whereas, the lower bamboo’s water absorbing ability the lower hydrolic conductivity’s value that obtained. Keywords : hydraulic conductivity , endurance , yellowbamboo